Families Role with Quality of Life (QOL) on Diabetes Mellitus Patients - Noer Saudah; Enny Virda Yuniarti; Eka Ayu Wulandari (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2019)
Diabetes Mellitus was a disease that not only requires treatment but also lifestyle changes, so that often patients tend to despair with a long therapy program that will have an impact on the quality of life of patients. This study aims to determine the relationship of family roles with quality of life (QOL) in patients with Diabetes Mellitus. Design of this study was cross sectional analytic type. The population in this study were all patients with diabetes mellitus and family on May-July 2018 at Dr Wahidin Sudiro Husodo General Hospital in Mojokerto as many as 96 people. Sample selection  done by purposive sampling as many as 57 respondents. Independent variable was family roles. Dependent variable was quality of life. The instrument used a questionnaire on family roles and quality of life. By used the Spearman statistical test. The results showed that almost half of the respondents had enough family roles as many as 32 respondents (56.7%), almost all respondents had a high quality of life of 38 respondents (66.7%), and the results of p <α = 0.05 are 0.046 <0.05. There was a relationship between the role of family and quality of life in patient with diabetes mellitus. The role of a good family can improve the quality of life of patients with Diabetes Mellitus. The better the role of the family, the higher the level of quality of life of the sufferer. Therefore the family can play a role in improving the quality of life Diabetes Mellitus sufferers.